Flavouring group evaluation 418 (FGE. 418): 3‐[3‐(2‐isopropyl‐5‐methyl‐cyclohexyl)‐ureido]‐butyric acid ethyl ester - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of 3‐[3‐(2‐isopropyl‐5‐methyl‐cyclohexyl)‐ureido]‐butyric acid ethyl ester [FL‐no: 16.136] as a new flavouring substance, in accordance with Regulation (EC) No 1331/2008. The substance has not been reported to occur naturally and it is chemically synthesised. The information provided on the manufacturing process, the composition and the stability of [FL‐no: 16.136] was considered sufficient. The chronic dietary exposure to [FL‐no: 16.136] estimated using the added portions exposure technique (APET) is calculated to be 860 μg/person per day for a 60‐kg adult and 540 μg/person per day for a 15‐kg 3‐year‐old child. [FL‐no: 16.136] did not show genotoxic effects in bacterial mutagenicity and mammalian cell micronucleus assays in vitro. No ADME studies on [FL‐no: 16.136] were provided. In a prenatal developmental toxicity study, no maternal or fetal toxicity was observed in rats dosed up to 1000 mg/kg body weight (bw) per day. In a 90‐day toxicity study in rats, no adverse effects were observed. In this study, the Panel considered that the NOAEL is 777 and 923 mg/kg bw per day (the highest dose tested) for male and female rats, respectively. Considering the lowest NOAEL of 777 mg/kg bw per day, as a reference point, adequate margins of exposure of 55 × 103 and 21 × 103 were calculated for adults and children, respectively, when considering the chronic APET dietary exposure estimates. The Panel concluded that the use of 3‐[3‐(2‐isopropyl‐5‐methylcyclohexyl)‐ureido]‐butyric acid ethyl ester [FL‐no: 16.136] as a flavouring substance under the proposed conditions of use does not raise a safety concern at the dietary exposure estimates calculated using the APET approach.